Reforming welfare states - Peter Huber; Thomas Leoni; Hans Pitlik (WWWforEurope, 2013)
This report collects and draws conclusions from research papers of Area 1. It summarises the results against the background of the existing literature, focusing in particular on the challenges arising on welfare states from globalisation, post-industrialisation, and demographic changes. The report also discusses problems of the political economy of policy reform and large-scale economic and social transitions.
Keywords: 330; Sozialstaat; Sozialreform